Analisis Efektivitas Penghimpunan Dana ZIS Pada Laznas Baitulmaal Muamalat: Studi Komparasi Penghimpunan Digital dan Non Digital - Nuraini, Annisa; Priyatno, Prima Dwi (JES (Jurnal Ekonomi Syariah), 2024)
ZIS (Zakat, Infaq, and Sedekah) has enormous potential in Indonesia. However, the current collection realization is still far from the existing potential. In general, each OPZ carries out two ways of collecting, namely directly and indirectly. This study aims to analyze the effectiveness of digital and non-digital collection at LAZNAS BMM. The method used in this research is descriptive qualitative method and case study approach with data collection techniques in the form of interviews, observation, and documentation. The effectiveness theory used is that of Sujadi F.X which has 5 indicators consisting of effectiveness, economy, accountable work implementation, real division of labor, and practical work procedures. The results of the study show that digital ZIS fundraising has been effective in the aspects of effectiveness, economy, accountable work implementation, and practical work procedures and for the real aspect of division of labor has not achieved effectiveness. Meanwhile, non-digital ZIS fundraising has been effective in terms of effectiveness, accountable work implementation, and real division of labor. For aspects that have not reached effectiveness, namely economics and practical work procedures. Overall, collecting ZIS funds digitally at Laznas BMM is more effective than non-digital collection. However, both digital and non-digital collections both have an important role in increasing the receipt of ZIS funds at Laznas BMM.